Laysa Kamithlihi Shay'un: The Interpretation of Mutashabihat Verses And Traditions By 'Abd Al-Qadir Wangah In Risalah Manhaj Ahl Al-Sunnah - Wan Mohd Fazrul Azdi Wan Razali; Syed Salim Syed Shamsuddin; Aziz, Mohammad Aizuddin Abdul; Mohamed, Mohd Faisal (Univ Malaya, Acad Islamic Studies, 2024)
Among many issues discussed and debated in the field of Islamic theology is the interpretation of the mutashabihat verses and traditions. Tuan Guru 'Abd Al-Qadir Wangah, or known as Ayah Dir Sekam, was among the many Malay Muslim scholars who analysed, described and contributed to the proper understanding of mutashabihat in the Islamic studies. This study aims at analyzing Ayah Dir's discussion on the interpretation of the mutashabihat from his writing, namely Risalah Manhaj Ahl al-Sunnah. Textual analysis methodology is applied on this 'Risalah' to thematize and organize his main ideas in providing the correct methodology in understanding the mutashabihat verses and traditions. Findings show that Ayah Dir Sekam's methodology of interpretation, namely ta'wil ijmali and tafsili, is in line with the methodology of classical and modern scholars of Ahl al-Sunnah wa al-Jama'ah, which is regarded as the mainstream of Islam. This is due to his strong link with the significant turath (heritage) and mu'tabar (credible) writings by these scholars. In the same way, this is also due to his firm educational experience with many well-known Malay Muslim scholars either in the Malay Archipelago or in Mecca.